Rotary-Prijs : Wedstrijd voor jonge kunstenaars. - Martens, Hugo; Hoet, Jan; Martens, Luc; Museum van Hedendaagse Kunst, Gent (Gent : Rotary Club Gent-Noord, 1995)
Ooms, David ; Claerbout, Mark ; Peeters, Elke ; Voets, Rudy ; Dhaenens, Renke ; Crutelle, Sylvie ; Derden, Majella ; De Sloover, Isabelle ; D'Hoogh, Walter ; Divjak, Milenko ; Dufoort, Rebecca ; Faes, Jozef ; Fischer, Marc ; Goris, Katrin ; et al.
Rotary Prijs '95, Museum van Hedendaagse Kunst, Gent, 30 september - 29 oktober 1995
kunstcatalogus